Characterisation of an RZ-DQPSK transmitter using coherent detection - Schmauß, Bernhard; Fludger, C.R.S.; Voß, Axel; Duthel, T.; Schulien, C. (ECOC September, 2007)
We characterise the optical field from an RZ-DQPSK transmitter using coherently detected constellation diagrams. We show the dependence on bias and phase offsets, as well as timing mismatch.
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.charac